FABP4 blocker attenuates colonic hypomotility and modulates white adipose tissue‐derived hormone levels in mouse models mimicking constipation‐predominant IBS. Issue 5 (20th December 2017) - Mosińska, P.; Jacenik, D.; Sałaga, M.; Wasilewski, A.; Cygankiewicz, A.; Sibaev, A.; Mokrowiecka, A.; Małecka‐Panas, E.; Pintelon, I.; Storr, M.; Timmermans, J. P.; Krajewska, W. M.; et al.
Abstract: Background: The role of fatty acid binding protein 4 (FABP4) in lower gastrointestinal (GI) motility is unknown. We aimed to verify the effect of inhibition of FABP4 on GI transit in vivo, and to determine the expression of FABP4 in mouse and human tissues. Methods: Fatty acid binding protein 4 inhibitor, BMS309403, was administered acutely or chronically for 6 and 13 consecutive days and its effect on GI transit was assessed in physiological conditions and in loperamide‐induced constipation. Intracellular recordings were made to examine the effects of BMS309403 on colonic excitatory and inhibitory junction potentials. Abdominal pain was evaluated using behavioral pain response. Localization and expression of selected adipokines were determined in the mouse colon and serum using immunohistochemistry and Enzyme‐Linked ImmunoSorbent Assay respectively. mRNA expression of FABP4 and selected adipokines in colonic and serum samples from irritable bowel syndrome (IBS) patients and control group were assessed. Key Results: Acute injection of BMS309403 significantly increased GI motility and reversed inhibitory effect of loperamide. BMS309403 did not change colonic membrane potentials. Chronic treatment with BMS309403 increased the number of pain‐induced behaviors. In the mouse serum, level of resistin was significantly decreased after acute administration; no changes in adiponectin level were detected. In the human serum, level of adiponectin and resistin, but not of FABP4, were significantly elevated in patients with constipation‐IBS (IBS‐C). FABP4 mRNA expression was significantly downregulated in the human colon in IBS‐C. Conclusions and Inferences: Fatty acid binding protein 4 may be involved in IBS pathogenesis and become a novel target in the treatment of constipation‐related diseases. Abstract : Relative mRNA expression of fatty acid binding protein 4 (FABP4) in colonic biopsies of patients with constipation‐predominant irritable bowel syndrome (IBS‐C) vs healthy subjects (control).